Rice yield penalty and quality deterioration is associated with failure of nitrogen uptake from regreening to panicle initiation stage under salinity - Li, Yusheng; Ai, Zhiyong; Mu, Yixue; Zhao, Tingcheng; Zhang, Yicheng; Li, Lin; Huang, Zheng; Nie, Lixiao; Khan, Mohammad Nauman (Frontiers in Plant Science, 2023)
In recent years, the development and utilization of saline land for rice cultivation have effectively expanded grain productivity. Rice is a salt-sensitive crop, and the increasing salinity problem threatens rice yield and quality. Therefore, we conducted open field experiments to study the effect of salinity on different growth stages of rice. Irrigating saline treatment was conducted at three different growth stages: irrigating saline from the regreening stage to the panicle initiation stage (S1), irrigating saline from the panicle initiation stage to the flowering stage (S2), and irrigating saline from the flowering stage to the maturity stage (S3). Each treatment period lasted for about 30 days. At the same time, irrigating saline water from the regreening stage to the maturity stage (S4) treatment was added in 2022 to explore the performance of salt stress during the whole growth period of rice. Based on the treatment of these different saline irrigation growth periods, three saline concentrations were incorporated, including salinity 0‰ (T1), 3‰ (T2), and 6‰ (T3) concentrations. No irrigating saline during the whole growth period was also used as a control (CK). The results indicated that rice grain yield and quality were most sensitive to saline treatment during S1 among the three stress periods. At the S1 stage, salinity mainly reduced the nitrogen uptake, resulting in stunted plant growth, reducing tillering, yield, and yield components, and deteriorating the rice quality. Compared to the control, IEN (grain yield over the total amount of N uptake in plants at maturity) was more sensitive at the S1 stage than S2 and S3 stages under salinity. Furthermore, the findings of our study suggest that under salinity, rice growth is not only directly affected by the higher sodium (Na+) content in plants, but the higher concentration of Na+ reduced the ability of plants to uptake nitrogen. Thus, more attention should be paid to the field management of the S1 stage, the most sensitive stage during rice cultivation in salinized areas. It is necessary to avoid salt damage to rice during this period and ensure irrigation with precious freshwater resources.